Research on energy conservation of port public buildings. Issue 1 (July 2020) - Ying, Haining; Lu, Huiyu; Ren, Jie; Li, Kang; Chen, Jing
Abstract: Energy is the basis of the survival and development of human society, and the energy needed is increasing. Our building energy consumption accounts for a large proportion of total social energy consumption, so the research and development of building energy-saving technology is the top priority. The energy conservation and emission reduction of port public buildings should also be paid attention to. Domestic and foreign scholars' research on port energy conservation mainly focus on the management and planning of port construction, less on the specific energy conservation measures of port public buildings, staying at a relatively macro and overall level, and lack of detailed research on the function positioning, site selection and layout, and structural form of port public buildings.